Mutations in the leader sequence and initiation codon of the gene for ribosomal protein S20 (rpsT) affect both translational efficiency and autoregulation. - Parsons, G D (1988)
We have transferred the complete structural gene and part of the leader for ribosomal protein S20 of Escherichia coli to a controllable expression vector and have used oligonucleotide-directed mutagenesis to create mutations in the untranslated leader of the plasmid-borne gene. We have assayed for posttranscriptional regulation of the synthesis of S20 after inducing transcription of the mutant S20 mRNA from the expression vector. We found that two mutations lead to loss of feedback control of S20 synthesis: (i) a change of the initiation codon from UUG to AUG and (ii) a replacement of part of the S20 leader with a nonhomologous sequence including an AUG initiation codon. These mutations also lead to increases in both the intrinsic translational efficiency of the plasmid-encoded S20 mRNA in vitro and its half-life in vivo. A double mutation (GA to CT) at residues -3 and -4 relative to the initiation codon does not result in overproduction of S20. Rather, it reduces translational efficiency in vitro and mRNA stability in vivo. Our results demonstrate the fundamental importance of the UUG initiation codon in mediating autogenous repression of S20 synthesis.